Enhanced microscale heat transfer in macro geometries : effect of flow field - Siew, Dennis Weng Kin (2014)
With technology getting more advance, there has been a strong demand for new cooling methods to remove the heat dissipated particularly from the electrical components. It is expected that in the future, these electrical components will be able to generate over 1000 of heat flux, and conventional cooling techniques cannot be used for cooling. The most actively researched cooling techniques is the microchannel heat transfer. It was first applied by Tuckerman and Pease in 1981 who cooled a large-scale electronic circuits using forced convection of water flowing through microchannels. Since then, there have been numerous researches conducted on heat transfer in microchannels. However, complicated and costly manufacturing procedures are usually required when fabricating microchannels. Therefore, this research aims to the study enhanced microscale heat transfer on macro geometries by applying conventional manufacturing methods to create the microchannels.